Enhancing acute inflammatory and sepsis treatment: superiority of membrane receptor blockade - Mun, Seok-Jun; Cho, Euni; Kim, Hyo Keun; Gil, Woo Jin; Yang, Chul-Su (Frontiers in Immunology, 2024)
Conditions such as acute pancreatitis, ulcerative colitis, delayed graft function and infections caused by a variety of microorganisms, including gram-positive and gram-negative organisms, increase the risk of sepsis and therefore mortality. Immune dysfunction is a characterization of sepsis, so timely and effective treatment strategies are needed. The conventional approaches, such as antibiotic-based treatments, face challenges such as antibiotic resistance, and cytokine-based treatments have shown limited efficacy. To address these limitations, a novel approach focusing on membrane receptors, the initiators of the inflammatory cascade, is proposed. Membrane receptors such as Toll-like receptors, interleukin-1 receptor, endothelial protein C receptor, μ-opioid receptor, triggering receptor expressed on myeloid cells 1, and G-protein coupled receptors play pivotal roles in the inflammatory response, offering opportunities for rapid regulation. Various membrane receptor blockade strategies have demonstrated efficacy in both preclinical and clinical studies. These membrane receptor blockades act as early stage inflammation modulators, providing faster responses compared to conventional therapies. Importantly, these blockers exhibit immunomodulatory capabilities without inducing complete immunosuppression. Finally, this review underscores the critical need for early intervention in acute inflammatory and infectious diseases, particularly those posing a risk of progressing to sepsis. And, exploring membrane receptor blockade as an adjunctive treatment for acute inflammatory and infectious diseases presents a promising avenue. These novel approaches, when combined with antibiotics, have the potential to enhance patient outcomes, particularly in conditions prone to sepsis, while minimizing risks associated with antibiotic resistance and immune suppression.